Attitudes and intended behaviour to mental disorders and associated factors in catalan population, Spain: cross-sectional population-based survey - Aznar-Lou, Ignacio (BMC Public Health, 2016)
BACKGROUND: Mental disorders have a huge impact on the European population. Two of the main causes of this impact are stigma and discrimination. The aim of this paper is to assess the stigma regarding mental disorder in Catalonia and to explore factors associated with stigma. METHODS: Cross-sectional population-based survey of a representative sample of non-institutionalized adult population (n = 1872). We evaluated attitudes (CAMI: Authoritarianism, Benevolence and Support to Community Mental Health care) and intended behaviour (RIBS) regarding mental disorder and experience of discrimination. Higher scores showed more favourable attitudes and intended behavior. Mean values and percentiles of the scales were calculated. Multivariable regression models were used to assess factors associated with stigma. RESULTS: Mean authoritarianism, benevolence and support to community mental health scores corresponded to the 66th, 90th and 78th percentile, respectively. Mean RIBS score corresponded to the 76th percentile. More favourable attitudes were associated with being male, younger, having a higher education, being Spanish, having suffered a mental disorder and having contact with a person with a mental disorder.Similarly, more favourable intended behaviour was associated with being younger, having secondary education, having Spanish nationality, belonging to a higher social class and having contact with a person with a mental disorder. People with depression or anxiety showed lower discrimination experiences than people with other mental disorders. CONCLUSIONS: The levels of stigma were generally low among the Catalan population. However, efforts should be made to decrease stigma related to authoritarianism. Interventions addressed to reducing stigma should take into account other mental disorders apart from depression or anxiety. They should be focused on older, immigrant population, people with lower educational attainment and people who have not had contact with someone with a mental disorder.